The effect of alpha binaural beat music on orthodontic pain after initial archwire placement: A randomized controlled trial - Alia El ALY; Ismaeel HANSA; Donald J. FERGUSON; Nikhilesh R. VAID (Dental Press Editora, 2023)
ABSTRACT Objective: The objective of this article was to evaluate the effect of alpha binaural beat music on pain level after initial placement of a maxillary fixed appliance, compared to music without binaural beats (placebo) and no music (control). Methods: 60 patients undergoing maxillary fixed orthodontic appliance and initial archwire placement were randomly allocated into the three aforementioned groups. The pain level experienced was monitored for the following seven days, using the short-form McGill pain questionnaire (SF-MPQ). Results / Descriptors: Intensity of both sensory and psychological aspects of pain reduced significantly in the binaural beat music (BBM) group, compared to the control, after the 5th day. Statistically significant lower affective and total pain scores were also found on day 6 for the placebo group, compared to the control. Present Pain Intensity (PPI): Statistically significant lower scores were found between the BBM group and the control group from days 3 to 7. Statistically significant lower scores were also found between the placebo and the control groups on days 4, 5 and 6. Visual Analog Scale (VAS): Compared to the control group, the placebo group had a lower VAS score on day 4, and the BBM group had lower scores on days 6 and 7. Conclusions: There was a significant reduction of pain demonstrated in the BBM group, compared to the control, toward the end of the first week of treatment. There was no difference in reported pain between the BBM and placebo groups for any of the scores.